Is digital world accessible to all? A Comprehensive Review of Digital Accessibility Research (1996-2024) - Seungyeon Ha (International Telecommunications Society (ITS), 2024)
Digital accessibility is not static, but a dynamic process that actively interacts with both physical and digital contexts. This study provides a comprehensive overview of digital accessibility by analyzing 416 scholarly articles published from 1996 to 2024 from SCOPUS and Web of Science to capture digital accessibility in current context. First, a bibliometric analysis examines publication trends, including years, countries, affiliations, authors, and keywords, to identify overall trends and emerging themes. This is supplemented by a qualitative analysis of 80 selected articles, providing an in-depth understanding of current research themes. Additionally, the study collects and analyzes 70 relevant quotations to enhance conceptual understanding and provide a standardized definition of digital accessibility. The results offer an extensive overview of digital accessibility literature using both quantitative and qualitative method, providing both surface level and in-depth analysis of what is being discussed in digital accessibility in academia. It contributes to digital accessibility literature by providing a steppingstone as well as guidelines for future research.
Keywords: 330; Digital accessibility; Media accessibility; Web accessibility; Systematic literature review; Bibliometric analysis; Digital inclusion